The structural motivation of palatalization - Elisa Battisti; Ben Hermans (Fórum Linguístico)
This paper is about the structural motivation of the palatalization of coronal stops in Brazilian Portuguese (BP) and cross-linguistically. It aims to explain why (a) coronal stop consonants are the typical targets of the process, (b) coronal stops are the only targets of the process in BP, (c) the typical trigger of palatalization crosslinguistically is the coronal high vowel, (d) the only trigger of the process in BP is the coronal high vowel. We propose an internal structure of segments with abstract elements C and V (VAN DER HULST, 2005, 2011) and show that the consonantality of high front vocoids is the motivation of palatalization. The process tends to affect consonants which are similar to the trigger in structural terms. The proposal allows us to distinguish secondary and full palatalization (BATEMAN, 2007) structurally. It also explains the selection of trigger and targets of palatalization in BP, which results of full palatalization, a kind of palatalization which demands maximally identical trigger and targets.